2022
DOI: 10.3390/w14121967
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation Properties of Soil/Modified Bentonite Backfill in Salt Solution

Abstract: The consolidation properties of soil-bentonite (SB) backfills containing 20% of the weight of sodium-hexametaphosphate-modified calcium bentonite (SHMP-20CaB) and prepared with 0 mM to 1000 mM calcium chloride (CaCl2) solution were evaluated. The results indicated that both consolidation stress and CaCl2 concentration had significant effects on the consolidation behaviors of the SHMP-20CaB backfill. In general, an increase in consolidation stress resulted in a decrease in the void ratio (e) and in the coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the swelling performance of bentonite decreases with increasing ionic concentration in the pore solution 4,5 . For example, Ernesto 6 , Herber 7 , and Zhao 8 found that the swelling performance of FEBEX, MX-80, and GMZ bentonites decreases with higher concentrations of monovalent metal ions like K + and Na + .…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have shown that the swelling performance of bentonite decreases with increasing ionic concentration in the pore solution 4,5 . For example, Ernesto 6 , Herber 7 , and Zhao 8 found that the swelling performance of FEBEX, MX-80, and GMZ bentonites decreases with higher concentrations of monovalent metal ions like K + and Na + .…”
Section: Introductionmentioning
confidence: 94%
“…Another advantage of salt waste is its ability to crystallise and harden at the moment of moisture release. Salts belong to self-hardening materials [67]. Therefore, the introduction of additional components (binders/additives) or the use of another type of impact on the waste is the activation of the strength-gaining process.…”
Section: Backfill Componentsmentioning
confidence: 99%
“…The hardening process proceeds slowly as moisture evaporates. A saturated salt solution is used as a grouting fluid since the aggregate dissolves in water [67,68].…”
Section: Backfill Componentsmentioning
confidence: 99%
“…For properties on the transport of pollutants for the GCL, the diffusion coefficient (Dd) was 3 × 10 −10 m 2 /s [30]. The retardation factor (Rd) for linear adsorption was chosen as 15 [31]. Other related parameters are summarized in Table 3.…”
Section: Parametersmentioning
confidence: 99%
“…It could be seen that the breakthrough was made at the shallow 0.9 m depth in the overlapping area where the amount of concentration was more than 10% of the source concentration [32], with consideration that the depth of the groundwater table For properties on the transport of pollutants for the GCL, the diffusion coefficient (D d ) was 3 × 10 −10 m 2 /s [30]. The retardation factor (R d ) for linear adsorption was chosen as 15 [31]. Other related parameters are summarized in Table 3.…”
Section: Parametersmentioning
confidence: 99%